Real Estate Marketing Using Wechat Platform in China - Zhang, Jiahui (2016)
Recently, WeChat has become a very popular platform as Social Network Site (SNS). The purpose of the study is to investigate the relationship of the real estate marketing by using WeChat platform in China. There is the limited literature review in English based since most of the research is in Chinese based which regards towards the WeChat platform. Mass media, income and attitude will be the independent variables that used to discuss in this research. Through these three independent variables, the researchers will study js there any relationship between the VI and the willingness of the people to purchase the housing through the WeChat platform. The research methodology is used correlation which is a quantitative survey to study the relationship among the VI and DV. The non-probability convenience sampling method will be conducted during the distribution of the questionnaires. Income may have the highest influence towards the real estate marketing when using WeChat platform in China.